2006
DOI: 10.1007/s11249-006-9036-5
|View full text |Cite
|
Sign up to set email alerts
|

The contact behavior of elastic/plastic non-Gaussian rough surfaces

Abstract: A three-dimensional contact analysis was conducted to investigate the contact behavior of elastic-perfectly plastic solids with non-Gaussian rough surfaces. The effect of skewness, kurtosis and hardness on contact statistics and the effect of skewness and kurtosis on subsurface stress are studied. Non-Gaussian rough surfaces are generated by the computer with skewness, Sk, of )0.3, 0.0 and 0.3, and kurtosis, K, of 2.0, 3.0 and 4.0. Contact pressures and subsurface stresses are obtained by contact analysis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Lee and Ren [20] conducted a group of contact simulations with a wide range of surface topographical parameters for elastic-perfectlyplastic materials. The contact area and subsurface stress fields have been extensively investigated for various statistical parameters of surface roughness and material hardness in [21,22]. Wang et al [23] presented an improved macro-micro approach to model the rough-surface contact in mixed lubrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Ren [20] conducted a group of contact simulations with a wide range of surface topographical parameters for elastic-perfectlyplastic materials. The contact area and subsurface stress fields have been extensively investigated for various statistical parameters of surface roughness and material hardness in [21,22]. Wang et al [23] presented an improved macro-micro approach to model the rough-surface contact in mixed lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…A two-dimensional digital filtration technology has been developed by Hu and Tonder [26] to generate random surfaces with specified ACF and the first four order statistical moments, which can be retrieved from digital surfaces sampled by a modern measurement device. The influence of the non-Gaussian features of an asperity height distribution on contact behaviors has been discussed by several authors in [6,7,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Smooth surfaces are rare in Nature (Majumdar and Bhushan, 1991), while rough ones have many useful properties ("rough skin is good" for suppressing air turbulence, see Monroe, 2006;Fransson et al, 2006). Roughness has a considerable effect on the contact of surfaces (Borri-Brunetto et al, 1999); it can influence adhesion (Wang et al, 2008), friction (Kim et al, 2006), wear , and reflection (Verhoest et al, 2008). While surface roughness has a positive effect in increasing adhesion it is considered as an undesirable imperfection from the point of view of friction (Chandrasekaran and Sundararajan, 2004;Jensen, 2006).…”
Section: Complexity Criticality and Roughnessmentioning
confidence: 99%
“…While surface roughness has a positive effect in increasing adhesion it is considered as an undesirable imperfection from the point of view of friction (Chandrasekaran and Sundararajan, 2004;Jensen, 2006). In each of these examples a small change in the distribution of heights, widths, or curvatures of the peaks has an important effect on the rough surface's behavior (Kim et al, 2006). Light scattering from optical coatings is the best example for how strongly processes could be affected by the roughness of interfaces (Germer, 2000).…”
Section: Complexity Criticality and Roughnessmentioning
confidence: 99%
“…Half-space models can be used to research non-Gaussian rough surfaces as shown by Kim et al [14], normal contact between a rough surface and a rigid sphere as shown by Tian and Bhushan [15] or the contact of fractal surfaces as shown by Willner [16].…”
Section: Introductionmentioning
confidence: 99%